(untitled) (Journal of Dhaka National Medical College & Hospital, 2012)
Diffuse gallbladder wall thickening is a nonspecific alteration caused by both intrinsic and extracholecystic diseases. The incidence of gallbladder illness in our country is increasing day by day. Details morphological and histomorphological knowledge is essential for proper diagnosis & management of the gallbladder diseases. This is a cross sectional descriptive type of study which was carried out in the Department of Anatomy, Sir Salimullah Medical College, Dhaka from July 2010 to June 2011. The number of sample was 62 postmortem human gallbladder which were collected from unclaimed dead bodies of the morgue of Dhaka Medical College and Sir Salimullah Medical College. The samples were divided into three different age groups. Morphological study was carried out on all samples by fine dissection method and histomorphological study was carried out on 18 relatively fresh samples by light microscopic method. There was statistically significant difference found when values were compared between different age groups. This study has revealed an age related change in the thickness of the gallbladder wall. DOI: http://dx.doi.org/10.3329/jdnmch.v18i1.12238 J. Dhaka National Med. Coll. Hos. 2012; 18 (01): 34-38